Substance use and misuse among college students: Results of an online survey from three neighboring cities of North India - Neha Jaswal; Chandrima Naskar; Abhishek Ghosh; Savita Prashar; Manoj Kumar (Indian Journal of Psychiatry)
We estimated prevalence and severity of substance use in college students from three cities in North India and explored demographic correlates of substance use. This was a cross-sectional online survey. We used Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST). We contacted respondents through social groups. We performed analyses from the original sample, bootstrapped samples, and random subsamples. A total of 229 (58.3%) respondents reported any lifetime substance use. A third of substance-using respondents were female. Alcohol (54.7%), tobacco (40.2%), and cannabis (15%) use were most commonly reported. Prevalence estimates did not differ between original and subsample analyses. A significant proportion of respondents (alcohol 29.7% and amphetamines 66.7%) were at moderate risk level. Male gender, family history of substance use, and commerce stream correlated with substance use. There were positive correlations between tobacco and alcohol and licit and illicit substance use. The study highlights the need for a comprehensive college substance misuse prevention policy.